Pengaruh Pengawasan dan Kepercayaan terhadap Produktivitas Kepala Sekolah SD Negeri di Kota Bekasi - Hermawan, Yudi (Jurnal Inovasi Pendidikan MH Thamrin, 2018)
The objective of this research is to know the effect of emotion and job stress toward contra productive work behaviour of the teachers at State Elementary School at Bekasi District. TheÂ research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 134 teachers. Research samples selected as much as 100 teachers using simple random sampling technique. The data obtained through questionnaires and analysed using path analysis techniques. Based on the results of data analysis in this research it is concluded: (1) the emotion has positive direct effect to contra productive work behaviour; (2) the job stress has positive direct effect to contra productive work behaviour; (3) the emotion has positive direct effect to job stress. The contra productive work behaviour can be improved through improvement of emotion and the job stress.